Assessment methods determining the higher education students’ academic success - Costa, J. M. (2021)
It is well known that academic success of undergraduate students depends on a variety of factors; several of them are external to their higher education institution. However, it is crucial to reflect on the impact of the factors controlled by the higher education institution (e.g., faculty or college) that can influence their success and achievement, including the assessment methods. To this end, this study analyzes the extent to which the assessment methods have a substantial impact on approval rates of students. In doing so, 797 averages of course grades from a Portuguese higher education institution were collected in different academic years between 2013/2014 and 2017/2018. The significance effect of the course field, laboratories, projects, mini-tests, group work, individual work, frequencies, exercises, and presentations on the final averages of the courses was evaluated based on the modeling of structural equations. The results showed that the use of laboratories, presentations, individual and group-based works/tasks are the most explanatory elements (25%) for positive averages. The remainder is justified by other factors associated with students, such as socio-economic, previous education, and motivational factors that explain academic success. In future work, the proposed model, with different teaching strategies, could be studied and evaluated within different educational contexts.